2017
DOI: 10.3851/imp3256
|View full text |Cite|
|
Sign up to set email alerts
|

DARING-B: Discontinuation of Effective Entecavir or Tenofovir Disoproxil Fumarate Long-Term Therapy before HBsAg Loss in Non-Cirrhotic HBeAg-Negative Chronic Hepatitis B

Abstract: Our prospective study shows that effective ≥4-year entecavir/TDF therapy can be safely discontinued in non-cirrhotic HBeAg-negative CHB patients. The probability of relapse is decreasing after month 6. Despite common virological relapses, most patients, particularly those with mild-moderate pretreatment fibrosis, remain without retreatment, at least in the first 18 months, as a substantial proportion of them clear HBsAg and the majority eventually enters into inactive carrier state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
130
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(139 citation statements)
references
References 23 publications
5
130
0
4
Order By: Relevance
“…This study echoed the findings of a systematic review of predominantly Asian studies, which showed that the weighted probability of HBsAg seroclearance was only 2% . Several studies have now indicated that the relapse occurs later with entecavir than with TDF; whether this is related to the differences in NAs or ethnic groups warrants further investigation by prospective studies of different ethnicities …”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This study echoed the findings of a systematic review of predominantly Asian studies, which showed that the weighted probability of HBsAg seroclearance was only 2% . Several studies have now indicated that the relapse occurs later with entecavir than with TDF; whether this is related to the differences in NAs or ethnic groups warrants further investigation by prospective studies of different ethnicities …”
Section: Discussionsupporting
confidence: 76%
“…whether this is related to the differences in NAs or ethnic groups warrants further investigation by prospective studies of different ethnicities. 28,29 Functional cure further improves the prognosis of CHB patients who have achieved complete viral suppression as shown in our recent territory-wide cohort study of 20 263 NA-treated patients, as…”
Section: Safety Of Stopping Namentioning
confidence: 78%
“…47,54,55 Small studies in Europe have reported rates of HBsAg loss as high as 20-30% within 3 years of stopping NAs, whereas studies in Asia have reported lower rates of HBsAg loss (<10%) after similar durations of off-treatment follow-up. [54][55][56][57][58][59] Moreover, clinical relapse, hepatitis flares, and hepatic decompensation can occur when NAs are stopped. 60 (Fig.…”
Section: Current Therapies For Chronic Hbv and Hdv Infectionmentioning
confidence: 99%
“…At baseline, 337 (13.9%) of the 2433 patients with cirrhosis (information of cirrhosis was not reported in two studies [24,27], including 140 off-NAs patients), which was diagnosed by histology ndings and/or imaging studies. [32], entecavir in three [23,24,28], tenofovir in two [20,34], several NAs in fteen [19,21,22,26,30,31,33,[35][36][37][38][39][40][41]44], and NAs was not reported in the remaining ve studies [25,27,29,42,43] ( Table 1).…”
Section: Studies Characteristicsmentioning
confidence: 99%
“…Only HBeAg-positive patients were involved in three studies [25,26,43], only HBeAg-negative patients in ten [20,29,31,32,[34][35][36][37][38]42], and both HBeAg-positive and HBeAg-negative patients in thirteen [19,21,23 Table 2). The shortest duration of follow up after NAs cessation was 12 months, and the longest was 62 months.…”
Section: Studies Characteristicsmentioning
confidence: 99%